PENGOLAHAN LIMBAH PANEN ROSELA (Hibiscus sabdariffa) DENGAN PRODUKSI DODOL - Yustina Wuri Wulandari (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2009)
ABSTRACT Rosela (Hibiscus sabdariffa) was one kind of hortikultura plants have cultivated in Jelok-Cepogo-Boyolali by SEGER ASRI Groups farmer. Animal husbandry of cows were supporting agro-industry rosella in this region. Therefore the specifically product rosella from Jelok were organic product. Rosela with small size was waste of post harvest so that condition need of handling and the solution was produced by dodol poduct. That product has long live time and with high nutrition in product will be impact to food healthy. The development of new entrepreneurship in Jelok will be support to increase welfare of public because dodol product have higher price. Key words : rosella calyx, dodol, and Jelok